2002
DOI: 10.1016/s0166-4328(02)00111-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a relationship between cage stereotypies and behavioural disinhibition in laboratory rodents

Abstract: Cage stereotypies */abnormal, repetitive, unvarying and apparently functionless behaviours */are common in many captive animals, sometimes resulting in self-injury or decreased reproductive success. However, a general mechanistic or neurophysiological understanding of cage stereotypies has proved elusive. In contrast, stereotypies in human mental disorder, or those induced by drugs or brain lesions, are well understood, and are thought to result from the disinhibition of behavioural selection by the basal gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
165
2
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(182 citation statements)
references
References 56 publications
13
165
2
2
Order By: Relevance
“…A further result of interest was that impaired behavioural inhibition (as would induce perseveration) was statistically independent of the frustration-related measures. In addition, in contrast with other studies that have found a relationship between stereotypic and perseverative behaviour [11,61] it had no main effects on stereotypic behaviour, nor did it increase the variance explained in the multiple regression models. However, it usefully partitioned out variance in some GLM models, suggesting that it was playing some minor and subtle role in the aetiology of stereotypic behaviour.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…A further result of interest was that impaired behavioural inhibition (as would induce perseveration) was statistically independent of the frustration-related measures. In addition, in contrast with other studies that have found a relationship between stereotypic and perseverative behaviour [11,61] it had no main effects on stereotypic behaviour, nor did it increase the variance explained in the multiple regression models. However, it usefully partitioned out variance in some GLM models, suggesting that it was playing some minor and subtle role in the aetiology of stereotypic behaviour.…”
Section: Discussioncontrasting
confidence: 99%
“…[5,23,48]), does not predict their performance of stereotypic behaviour, and (b) our enriched-reared subjects display more normal behavioural inhibition, as inferred from perseveration under test (e.g. [52]) -a proxy measure of basal ganglia dysfunction [11,61] -than non-enrichedraised mice ('Protection Hypothesis'). In contrast, if early enrichment increases the stereotypic behaviour our subjects display after transfer to non-enriched conditions compared to mice raised in such conditions, we should find that (a) frustration post-transfer does predict their performance of stereotypic behaviour, while (b) behavioural inhibition should be no more normal in our enriched-reared subjects than in non-enriched-raised mice ('Frustration Hypothesis').…”
Section: Overall Aims and Rationalementioning
confidence: 78%
See 3 more Smart Citations